FACTORS WHICH AFFECT THE FATIGUE OF SWIMMERS - Dejan Madić; Tomislav Okičić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
Fatigue is an unplanned reduction or stagnation of the working ability over a longer period of time caused by the overstrain of the organism of a sportsman/woman, i.e it can be said that fatigue is a phenomenon which protects the organism from excessive and harmful exhaustion. In this paper the authors will explain the causes of fatigue and the value of different training programmes in increasing swimmer's tolerance to fatigue. It can be said that fatigue and exhaustion during swimming depend on the availability of energy, accumulation of metabolic harmful products and the limitation within the nervous system There is no factor solely responsible for the occurrence of fatigue.It is more likely that there is a multitude of causes that contribute to the feeling of uneasiness connected with fatigue and exhaustion during swimming;therefore, having this fact in mind any training has to be adjusted to individual abilities.